New cocalodine jumping spiders from Papua New Guinea (Araneae: Salticidae: Cocalodinae) - Maddison, Wayne P. (Zootaxa, 2009)
Six new species and three new genera of cocalodine jumping spiders are described. Restricted to New Guinea and nearby areas, the Cocalodinae are basal salticids, outside the major salticid clade Salticoida. The new genera are Yamangalea (type species Y. frewana, new species), Tabuina (type species T. varirata, new species) and Cucudeta (type species C. zabkai, new species). In addition to these type species, described are the new species Tabuina rufa, Tabuina baiteta, Cucudeta uzet, Cucudeta gahavisuka, and Allococalodes madidus. The first description of females of the genus Allococalodes is provided. Natural history observations and photographs of living specimens are provided for all five genera of cocalodines.